Unusual record of Pacific harbor seal (Phoca vitulina richardii) feeding on anchovy (Engraulis mordax) in the fishery of small pelagic fishes in the Gulf of California - Barba-Acuña, Isai; Gallo-Reynoso, Juan Pablo (Revista de Biología Marina y Oceanografía, 2019)
Pacific harbor seals (Phoca vitulina richardii) range in North America from Japan to Mexico. Here we report the first record of a Pacific harbor seal feeding on Northern anchovy (Engraulis mordax) inside a purse-seine net of a sardine fishing boat in the Gulf of California. This event was recorded on video on January 11th, 2010, near Estero Tortuga, Guasimas, Sonora (27°50’N, 110°39’W). Sea conditions were of El Niño Southern Oscillation; this record was likely due to El Niño, forcing seals to travel beyond their distribution range in search of alternate foraging areas.